Playing nice: a multi-methodological study on the effects of social conformity on memory - Deuker, Lorena; Müller, Anna R.; Montag, Christian; Markett, Sebastian; Reuter, Martin; Fell, Juergen; Trautner, Peter; Axmacher, Nikolai (Frontiers in Human Neuroscience, 2013)
Conformity is an important aspect of social behavior. Two main motives have been identified: people may adapt their behavior to “play nice” despite knowing better (normative conformity) or they may accept the others’ opinion as a valid source of information (informative conformity). Neuroimaging studies can help to distinguish between these two possibilities. Here, we present a functional magnetic resonance imaging (fMRI) study on memory conformity in a real group situation. We investigated the effects of group pressure on activity in hippocampus and anterior cingulate cortex (ACC) which likely support informative and normative memory conformity, respectively. Furthermore, we related the single nucleotid polymorphism (SNP) rs4680 (called COMT Val158Met) on the gene coding for Catechol-O-methyltransferase (COMT) to both behavior and fMRI activation. Homozygous Met-allele carriers (Val-) behaved more conformist than carriers of at least one Val-allele (Val+). In the neuroimaging data, we compared trials in which subjects were confronted with a majority of incorrect group responses to trials in which they were confronted with a majority of correct group responses. We found increased hippocampal activity when the majority of the group was correct, possibly indicating retrieval processes. Moreover, we observed enhanced activity in the ACC when the majority of the group was incorrect, suggesting that conformity was mostly normative. Most interestingly, this latter effect was more pronounced for Val- as compared to Val+ participants. This offers a speculative explanation for the higher behavioral levels of social conformity in Val- allele carriers, because their subjectively perceived conflict in the presence of an incorrect group majority may have been higher. Overall, this study demonstrates how the mechanisms leading to complex social behavior such as conformity can be studied by combining genetic analyses and fMRI in social neuroscience paradigms.